Preliminary assessment of Hedychium coronarium essential oil on fibrinogenolytic and coagulant activity induced by Bothrops and Lachesis snake venoms - Miranda, Cíntia A SF (J Venom Anim Toxins Incl Trop Dis, 2014)
BACKGROUND: The search for new inhibitors of snake venom toxins is essential to complement or even replace traditional antivenom therapy, especially in relation to compounds that neutralize the local effects of envenomations. Besides their possible use as alternative to traditional antivenom therapy, some plant species possess bioactive secondary metabolites including essential oils, which can be extracted from weeds that are considered substantial problems for agriculture, such as Hedychium coronarium. METHODS: The essential oils of leaves and rhizomes from H. coronarium were extracted by hydrodistillation, and their potential inhibitory effects on the coagulant and fibrinogenolytic activities induced by the venoms of Lachesis muta, Bothrops atrox and Bothrops moojeni were analyzed. Citrated human plasma was used to evaluate the clotting time whereas changes in fibrinogen molecules were visualized by electrophoresis in polyacrylamide gel. The experimental design used for testing coagulation inhibition was randomized in a 3 × 2 factorial arrangement (concentration × essential oils), with three replications. The essential oils were compared since they were extracted from different organs of the same botanical species, H. coronarium. RESULTS: The results suggest that the oils interact with venom proteases and plasma constituents, since all oils evaluated, when previously incubated with venoms, were able to inhibit the clotting effect, with less inhibition when oils and plasma were preincubated prior to the addition of venoms. CONCLUSIONS: Thus, after extensive characterization of their pharmacological and toxicological effects, the essential oils can be used as an alternative to complement serum therapy, especially considering that these plant metabolites generally do not require specific formulations and may be used topically immediately after extraction.